EFEKTIVITAS TERAPI MUSIK KLASIK TERHADAP PENURUNAN TINGKAT HALUSINASI PADA PASIEN HALUSINASI PENDENGARAN DI RUMAH SAKIT JIWA PROF. DR.M. ILDREM MEDAN TAHUN 2020 - Dian Anggri Yanti; Abdi Lestari Sitepu; Kuat Sitepu; Pitriani .; Wina Novita Br Purba (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
Increased illness causes problems in the health field one misbehaving in the from of auditory hallucinations. This can be overcome with pharmacological and non-pharmacological therapies. Non pharmacological therapy which can be used in the form of classical music therapy. The purpose of this research is to find out the effectiveness of classical music therapy to decrease the level of hallucinations in patients with auditory hallucinations. Type of this research is quantitative research uses quasi-experimental design with design research pre and post test without control. Sampling techniques in this study using a sample with a population of 22 respondents at Mental Hospital Prof. Dr. M. Ildrem Medan in 2020. The results of statistical analysis using the Paired t test indicates p value of 0,000 means that there is effectiveness in the administration of classical music therapy to decrease the level of hallucinations in patients with auditory hallucinations. The result is expected of music therapy to be one nursing intervention to decrease level hallucination with auditory of hallucination. Keywords: Patients with hallucination, music therapy, level of auditory Hallucination.